1984
DOI: 10.1080/00071668408454894
|View full text |Cite
|
Sign up to set email alerts
|

Energy and nitrogen metabolism of broilers selected over ten generations for increased growth rate, food consumption and conversion of food to gain

Abstract: Energy and nitrogen (N) metabolism were studied in 6-week-old male birds taken from 4 lines of chickens selected for 10 generations for increased weight gain (line W), increased food consumption (line F), increased conversion of food to gain (line E) or at random (controls, line C). Calorimetric measurements were made 8 times on each line while fed ad libitum in large open-circuit respiration chambers for 3 d, and 11 to 13 times without food in smaller closed-circuit respiration chambers for 24 h. The F line a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 10 publications
4
19
1
Order By: Relevance
“…The results of Lowe and Merkley [10] showed that body weight gains/food consumption ratios tended to favour the K/k + genotype, which our results suggest at 10 weeks, although not significantly. The effects of the k + gene observed by Pym et al [15] seem to agree with our observations.…”
Section: Than At 31supporting
confidence: 83%
“…The results of Lowe and Merkley [10] showed that body weight gains/food consumption ratios tended to favour the K/k + genotype, which our results suggest at 10 weeks, although not significantly. The effects of the k + gene observed by Pym et al [15] seem to agree with our observations.…”
Section: Than At 31supporting
confidence: 83%
“…However, it may seem unlikely, as an overarching factor on which energy use efficiency is dependant, that this would have remained suboptimal after natural selection. Elsewhere, protein turnover has been credited to account for anywhere up to 30 % of broiler heat production, prompting some research into the genetic potential of reducing it (Millward et al 1976;Muramatsu et al 1987;Pym et al 1984). There has been some indication that higher protein accretion rates are achievable through selection by lowering protein degradation rates (Tomas et al 1988(Tomas et al , 1991.…”
Section: Metabolic Activitymentioning
confidence: 99%
“…There have been attempts to quantify the differences in the metabolic heat production rate between different broiler breeds (e.g. Pym et al 1984), and it has been suggested that it is lower in breeds selected for high feed efficiency or high weight gain than birds selected for high feed intake. Pym and Farrell (1977) showed the fasting metabolic heat production, indicative of the basal metabolic rate (Noblet et al 2013), to be 19 % higher in lines selected for high feed consumption when compared to a control line by using respiration chambers to carry out feeding experiments; this led to an estimated 10 % decrease in the feed use efficiency (Carré et al 2008).…”
Section: Metabolic Activitymentioning
confidence: 99%
“…Pym et al (1984) found no differences in net N retention efficiency between broilers that had been selected for traits such as growth, food intake or FCR. Fractional rates of protein turnover did not differ between a line selected for high breast yield and a random bred control line (Pym et al, 2004).…”
Section: Efficiency Of Net Energy and Nutrient (Protein) Utilisationmentioning
confidence: 91%
“…Poultry Differences in (energy) maintenance requirements have been reported both between breeds of broilers and between breeds of laying hens. Whereas Geraert et al (1990) and Buyse et al (1998) have reported few differences in maintenance between broiler strains that have been selected against fatness, Pym et al (1984) have reported large differences between broilers that have been selected for traits such as growth, food intake or FCR. However, these differences were mainly due to the increased energy maintenance requirements of birds selected for food intake.…”
Section: Maintenance Requirementsmentioning
confidence: 99%